Wealth, health, and democracy in East Asia and Latin America - McGuire, James W. (New York : Cambridge University Press, 2010)
"Why do some societies fare well, and others poorly, at reducing the risk of early death? Wealth, Health, and Democracy in East Asia and Latin America finds that the public provision of basic health care and other inexpensive social services has reduced mortality rapidly even in tough economic circumstances, and that political democracy has contributed to the provision and utilization of such social services, in a wider range of ways than is sometimes recognized. These conclusions are based on case studies of Argentina, Brazil, Chile, Costa Rica, Indonesia, South Korea, Taiwan, and Thailand, as well as on cross-national comparisons involving these cases and others. James W. McGuire is professor in the Department of Government at Wesleyan University. He specializes in comparative politics with a regional focus on Latin America and East Asia and a topical focus on democracy and public health. He is the author of Peronism without Perón: Unions, Parties, and Democracy in Argentina and is a recipient of Wesleyan's Binswanger Prize for Excellence in Teaching"--Provided by publisher.
HKBU library
YT2025 M09
Keywords: Infants -- Mortality -- East Asia; Infants -- Mortality -- Latin America; East Asia -- Social policy; East Asia -- Economic policy; Latin America -- Social policy; Latin America -- Economic policy